Two new 2-alkylquinolones, inhibitory to the fish skin ulcer pathogen Tenacibaculum maritimum, produced by a rhizobacterium of the genus Burkholderia sp. - Li, Dandan; Oku, Naoya; Hasada, Atsumi; Shimizu, Masafumi; Igarashi, Yasuhiro (Beilstein Journal of Organic Chemistry, 2018)
Exploration of rhizobacteria of the genus Burkholderia as an under-tapped resource of bioactive molecules resulted in the isolation of two new antimicrobial 2-alkyl-4-quinolones. (E)-2-(Hept-2-en-1-yl)quinolin-4(1H)-one (1) and (E)-2-(non-2-en-1-yl)quinolin-4(1H)-one (3) were isolated from the culture broth of strain MBAF1239 together with four known alkylquinolones (2 and 4–6), pyrrolnitrin (7), and BN-227 (8). The structures of 1 and 3 were unambiguously characterized using NMR spectroscopy and mass spectrometry. Compounds 1–8 inhibited the growth of the marine bacterium Tenacibaculum maritimum, an etiological agent of skin ulcers in marine fish, offering new opportunities to develop antibacterial drugs for fish farming.
Keywords: antimicrobial; Burkholderia; quinolone; skin ulcer; Tenacibaculum maritimum

(untitled) - Depoorter, E.; Bull, M. J.; Peeters, C.; Coenye, T.; Vandamme, P.; Mahenthiralingam, E. (Appl. Microbiol. Biotechnol., 2016)

(untitled) - Estrada-de los Santos, P.; Rojas-Rojas, F. U.; Tapia-García, E. Y.; Vásquez-Murrieta, M. S.; Hirsch, A. M. (Ann. Microbiol. (Heidelberg, Ger.), 2016)

(untitled) - Beukes, C. W.; Palmer, M.; Manyaka, P.; Chan, W. Y.; Avontuur, J. R.; van Zyl, E.; Huntemann, M.; Clum, A.; Pillay, M.; Palaniappan, K.; Varghese, N.; Mikhailova, N.; et al. (Front. Microbiol., 2017)

(untitled) - Rusch, A.; Islam, S.; Savalia, P.; Amend, J. P. (Int. J. Syst. Evol. Microbiol., 2015)

(untitled) - Revathy, T.; Jayasri, M. A.; Suthindhiran, K. (Scientifica, 2015)

(untitled) - Wang, Y.; Yin, B.; Hong, Y.; Yan, Y.; Gu, J.-D. (Ecotoxicology, 2008)

(untitled) - Suárez-Moreno, Z. R.; Caballero-Mellado, J.; Coutinho, B. G.; Mendonça-Previato, L.; James, E. K.; Venturi, V. (Microb. Ecol., 2012)

(untitled) - Yabuuchi, E.; Kosako, Y.; Oyaizu, H.; Yano, I.; Hotta, H.; Hashimoto, Y.; Ezaki, T.; Arakawa, M. (Microbiol. Immunol., 1992)

(untitled) - Mitchell, R. E.; Greenwood, D. R.; Sarojini, V. (Phytochemistry, 2008)

(untitled) - Brady, S. F.; Bauer, J. D.; Clarke-Pearson, M. F.; Daniels, R. (J. Am. Chem. Soc., 2007)

(untitled) - Ballio, A.; Barra, D.; Bossa, F.; DeVay, E. J.; Grgurina, I.; Iacobellis, N. S.; Marino, G.; Pucci, P.; Simmaco, M.; Surico, G. (Physiol. Mol. Plant Pathol., 1988)

(untitled) - Hoitink, H. A. J.; Sinden, S. L. (Phytopathology, 1970)

(untitled) - Hashimoto, M.; Hattori, K. (Chem. Pharm. Bull., 1967)

(untitled) - Mori, T.; Yamashita, T.; Furihata, K.; Nagai, K.; Suzuki, K.-i.; Hayakawa, Y.; Shin-ya, K. (J. Antibiot., 2007)

(untitled) - Staerk, D.; Kesting, J. R.; Sairafianpour, M.; Witt, M.; Asili, J.; Emami, S. A.; Jaroszewski, J. W. (Phytochemistry, 2009)

(untitled) - Wells, I. C. (J. Biol. Chem., 1952)

(untitled) - Moon, S.-S.; Kang, P. M.; Park, K. S.; Kim, C. H. (Phytochemistry, 1996)

(untitled) - Gerth, K.; Trowitzsch, W.; Wray, V.; Höfle, G.; Irschik, H.; Reichenbach, H. (J. Antibiot., 1982)

(untitled) - Itoh, J.; Amano, S.; Ogawa, Y.; Kodama, Y.; Ezaki, N.; Yamada, Y. (J. Antibiot., 1980)

(untitled) - Bisacchi, G. S. (J. Med. Chem., 2015)

(untitled) - Michael, J. P. (Nat. Prod. Rep., 2001)

(untitled) - Michael, J. P. (Nat. Prod. Rep., 2003)

(untitled) - Michael, J. P. (Nat. Prod. Rep., 2005)

(untitled) - Michael, J. P. (Nat. Prod. Rep., 2007)

(untitled) - Michael, J. P. (Nat. Prod. Rep., 2008)

(untitled) - Dekker, K. A.; Inagaki, T.; Gootz, T. D.; Huang, L. H.; Kojima, Y.; Kohlbrenner, W. E.; Matsunaga, Y.; McGuirk, P. R.; Nomura, E.; Sakakibara, T.; Sakemi, S.; Suzuki, Y.; et al. (J. Antibiot., 1998)

(untitled) - Cheng, C.; Othman, E. M.; Reimer, A.; Grüne, M.; Kozjak-Pavlovic, V.; Stopper, H.; Hentschel, U.; Abdelmohsen, U. R. (Tetrahedron Lett., 2016)

(untitled) - Kunze, B.; Höfle, G.; Reichenbach, H. (J. Antibiot., 1987)

(untitled) - Vial, L.; Lepine, F.; Milot, S.; Groleau, M.-C.; Dekimpe, V.; Woods, D. E.; Deziel, E. (J. Bacteriol., 2008)

(untitled) - Long, R. A.; Qureshi, A.; Faulkner, D. J.; Azam, F. (Appl. Environ. Microbiol., 2003)

(untitled) - Hertiani, T.; Edrada-Ebel, R. A.; van Soest, R. W. M.; Sudarsono, P. (Indones. J. Pharm., 2008)

(untitled) - Heeb, S.; Fletcher, M. P.; Chhabra, S. R.; Diggle, S. P.; Williams, P.; Cámara, M. (FEMS Microbial. Rev., 2011)

(untitled) - Kitamura, S.; Hashizume, K.; Iida, T.; Miyashita, E.; Shirahata, K.; Kase, H. (J. Antibiot., 1986)

(untitled) - Moon, S. S.; Myung, E. J.; Cho, S. C.; Park, J. B.; Chung, B. J. (Korean J. Pest. Sci., 2002)

(untitled) - Lépine, F.; Milot, S.; Déziel, E.; He, J.; Rahme, L. G. (J. Am. Soc. Mass Spectrom., 2004)

(untitled) - Okada, B. K.; Wu, Y.; Mao, D.; Bushin, L. B.; Seyedsayamdost, M. R. (ACS Chem. Biol., 2016)

(untitled) - Wang, B.; Waters, A. L.; Sims, J. W.; Fullmer, A.; Ellison, S.; Hamann, M. T. (Microb. Ecol., 2013)

(untitled) - Depke, T.; Franke, R.; Brönstrup, M. (J. Chromatogr., B, 2017)

(untitled) - Avendaño-Herrera, R.; Toranzo, A. E.; Magariños, B. (Dis. Aquat. Org., 2006)

(untitled) - Oku, N.; Matsumoto, M.; Yonejima, K.; Tansei, K.; Igarashi, Y. (Beilstein J. Org. Chem., 2014)